Solve for t -11t=15-6t

Math
-11t=15-6t
Move all terms containing t to the left side of the equation.
Tap for more steps…
Add 6t to both sides of the equation.
-11t+6t=15
Add -11t and 6t.
-5t=15
-5t=15
Divide each term by -5 and simplify.
Tap for more steps…
Divide each term in -5t=15 by -5.
-5t-5=15-5
Cancel the common factor of -5.
Tap for more steps…
Cancel the common factor.
-5t-5=15-5
Divide t by 1.
t=15-5
t=15-5
Divide 15 by -5.
t=-3
t=-3
Solve for t -11t=15-6t

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top